Cyclo-oxygenase-2 selective inhibitors and nonsteroidal anti-inflammatory drugs: balancing gastrointestinal and cardiovascular risk - Moore, R; Derry, S; McQuay, H (BioMed Central, 2007)
Background: Differences between gastrointestinal and cardiovascular effects of traditional NSAID or cyclooxygenase-2 selective inhibitor (coxib) are affected by drug, dose, duration, outcome definition, and patient gastrointestinal and cardiovascular risk factors. We calculated the absolute risk for each effect. Methods: We sought studies with large amounts of information to calculate annualised rates for clearly defined gastrointestinal (complicated upper gastrointestinal perforations, ulcers, or bleeds, but not symptomatic or endoscopic ulcers) and serious cardiovascular outcomes (antiplatelet trial collaborators – APTC – outcome of fatal or nonfatal myocardial infarction or stroke, or vascular death). Results: Meta-analyses and large randomised trials specifically analysing serious gastrointestinal bleeding or cardiovascular events occurring with five different coxibs had appropriate data. In total there were 439 complicated upper gastrointestinal events in 49,006 patient years of exposure and 948 serious cardiovascular events in 99,400 patient years of exposure. Complicated gastrointestinal events occurred less frequently with coxibs than NSAIDs; serious cardiovascular events occurred at approximately equal rates. For each coxib, the reduction in complicated upper gastrointestinal events was numerically greater than any increase in APTC events. In the overall comparison, for every 1000 patients treated for a year with coxib rather than NSAID, there would be eight fewer complicated upper gastrointestinal events, but one more fatal or nonfatal heart attack or stroke. Three coxib-NSAID comparisons had sufficient numbers of events for individual comparisons. For every 1000 patients treated for a year with celecoxib rather than an NSAID there would be 12 fewer upper gastrointestinal complications, and two fewer fatal or nonfatal heart attacks or strokes. For rofecoxib there would be six fewer upper gastrointestinal complications, but three more fatal or nonfatal heart attacks or strokes. For lumiracoxib there would be eight fewer upper gastrointestinal complications, but one more fatal or nonfatal heart attack or stroke. Conclusion: Calculating annualised event rates for gastrointestinal and cardiovascular harm shows that while complicated gastrointestinal events occur more frequently with NSAIDs than coxibs, serious cardiovascular events occur at approximately equal rates. For each coxib, the reduction in complicated upper gastrointestinal events was numerically greater than any increase in APTC events.